[Halliburton / Brown & Root Report] - Brown & Root Civil - GeoJet Foundation System - I. Introduction - Gordon] [Reavis (Deep Foundations Institute, 1993)
Halliburton Services and Brown & Root have developed a unique foundation system that blends oilfield and construction technologies to construct deep foundations which offer significant advantages across a variety of soil profiles. This highly efficient system is being developed to meet the construction industry's needs into the 21st Century. Based on a concept initially introduced to Halliburton Services by V.L. Schellhorn in 1987, Halliburton combined their existing cement slurry mixing and pumping technology with oilfield drilling practices and a new tool design to field test the viability of the concept. Results looked encouraging, and Halliburton asked it's sister company, Brown & Root to evaluate and further develop the process. With Brown & Root's knowledge of the construction industry, the original concept has developed into a viable and efficient foundation construction system.